Internet use and health status among older adults: The mediating role of social participation - Hou, Bin; Li, Yumei; Wang, Haixia (Frontiers in Public Health, 2022)
(1) Background: The acceleration of population aging and the arrival of the informatization make more and more older adults use the Internet, and its use is having an impact on their health. However, the relationship between internet use and the health of older adults and the mechanism of the effect of internet use on the health are not very clear. (2) Methods: Multiple linear regression models to explore the correlation between internet use and health status in the 3,141 individuals aged ≥60 years were used. Propensity score matching (PSM) method was used to test the robustness of the regression results. In addition, sequential recursive models was used to examine the mediating effect of social participation on the relationship between internet use and health status. (3) Results and discussion: We found a significant positive relationship between internet use and health status, and social participation mediated the relationship between internet use and health status. In addition, the effect of internet use on health status was different among older adults in rural and urban areas. (4) Conclusions: The development and application of internet products adapted to the development of an aging society should be accelerated to meet their needs for continued socialization. The forms and activities of social participation for the elderly groups should be enriched and public service internet usage training seminars should be conducted to improve internet skills.